2014
DOI: 10.2807/1560-7917.es2014.19.29.20859
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for outbreaks of gastroenteritis in elderly long-term care facilities in France, November 2010 to May 2012

Abstract: reported through the surveillance system for gastroenteritis outbreaks in LTCF. A total of 1,072 outbreaks were reported, causing 26,551 episodes of illness and 60 deaths. The median attack rate (AR) among residents was 32%. Norovirus and person-to-person transmission were the most frequently reported aetiology and mode of transmission. Control measures were implemented in 1,054 (98%) outbreaks and for 928 outbreaks, the timing of such measures could be inferred. Of these, 799 (86%) had put control measures in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 19 publications
7
34
0
Order By: Relevance
“…The infection rates observed here were similar to those found in previous studies of NoV and Influenza outbreaks (odds of being infected during a Flu+ outbreak were around 40% less than during a NoV+ outbreak). Reported infection rates were close to 30.0% in influenza outbreaks and 40.0% in NoV outbreaks [18][19][20].…”
Section: Discussionmentioning
confidence: 81%
“…The infection rates observed here were similar to those found in previous studies of NoV and Influenza outbreaks (odds of being infected during a Flu+ outbreak were around 40% less than during a NoV+ outbreak). Reported infection rates were close to 30.0% in influenza outbreaks and 40.0% in NoV outbreaks [18][19][20].…”
Section: Discussionmentioning
confidence: 81%
“…Characteristics of the outbreaks are presented in Tables 2-4. Fifteen studies reported outbreaks caused by bacteria [15-17, 20, 22, 24, 27, 32-39] and 22 studies were outbreaks by viruses [14,18,19,21,23,25,26,[28][29][30][31][40][41][42][43][44][45][46][47][48][49][50]. The largest number of a single pathogen was influenza viruses [40][41][42][43][44][45], followed by group A streptococcus (GAS) [17,20,24,37,38].…”
Section: Characteristics Of the Outbreaksmentioning
confidence: 99%
“…The largest number of a single pathogen was influenza viruses [40][41][42][43][44][45], followed by group A streptococcus (GAS) [17,20,24,37,38]. The most affected site was respiratory tract (n = 12) [32, 35, 36, 39-45, 48, 50], followed by gastrointestinal (GI) tract (n = 10) [14,16,23,26,27,31,33,46,47,49]. Other sites including skin and soft tissue and eyes were affected.…”
Section: Characteristics Of the Outbreaksmentioning
confidence: 99%
“…Among the 46 remaining studies, 33 investigated multifaceted interventions which covered other aspects of infection control besides HH, 39,43,46,50,52,53,56,59,61,63,65 whereas 13 described interventions based on HH only. 10,45,[47][48][49]51,54,55,57,58,60,62,64 The interventions on HH were diverse and included educational programs for the staff and the residents (in 57% of the 46 studies describing interventions), 10,14,20,21,23,27,29,39,43,45,47,48,50,51,53,55-65 implementation of new guidelines (28% of studies), [10][11][12][13]15,17,19,20,22,26,…”
Section: Interventionsmentioning
confidence: 99%